Estimating Determinants of Sugarcane Production in Bihar : An Empirical Analysis - Aditi; Kumar, Raviranjan; Kumbhar, Rathi Kanta (Arthshastra Indian Journal of Economics & Research, 2024)
Purpose : The present study focused on identifying the factors that influence sugarcane production in Bihar. The increasing significance of cash crops such as sugarcane in the nation led us to examine the factors influencing sugarcane output in Bihar, one of the top-producing states of India, prior to its independence. Methodology : To analyze the time series data on Bihar’s sugarcane output, the area under cultivation, and sugar factories from 1950–1950 to 2020–2021 multiple linear regression model (MLRM) was used. When the number of sugar factories and the area under cultivation served as the explanatory factors, and production was the dependent variable. Findings : We found that the area under sugarcane and the number of operational sugar factories had an impact on sugarcane production. Both explanatory factors were found to be favorably connected to the dependent variable. Hence, the number of sugar factories and areas under sugarcane were important determinants of sugarcane production. Originality : In contrast to other studies on the factors influencing sugarcane output, the current work developed a model to investigate the variables influencing sugarcane production in Bihar. Practical Implications : Industrialists should take note of the study’s significant implications, and policymakers should use the study’s results to promote laws that encourage sustainable sugarcane farming methods and the expansion of Bihar’s industry as a whole. Although our study has limitations, it leaves room for more research because more variables might be taken into account.